Community Radio: Preferences, Opinion and Listening Behaviour of Farmers - N. V. Kumbhare , R. N. Padaria , Premlata Singh , Anjani Kumar and Sujit Sarkar, (Indian Journal of Extension Education, 2015)
Community radio is an innovative tool for community empowerment catering information needs of the farmingcommunity in rural and remote areas in a radius of about 15 kms. The study was conducted in purposively selected fivecommunity radio stations during 2012 to 2014. Five community radio stations i.e. CCSHAU, Hissar (Haryana), VallabhKrishak Radio, Saharanpur (Uttar Pradesh), Community Radio, Mewat (Haryana), Pravara Community Radio,Babhaleshwar (Maharashtra) and Sharda Community Radio, Baramati (Maharashtra) were selected for the study. Twovillages each were selected randomly from each CRS jurisdiction to see the farmers' responses about the community radiostation. Fifteen (15) respondents' were selected randomly from each of the sampled ten villages. Thus, a total of 150respondents from five CRS constituted the sample for the study. The study revealed that a majority (65 %) listenerspreferred agriculture success stories followed by live interactive programme (60 %), experts talk on agriculture and GKtest in agriculture (57.50%). Also a majority (52.67%) of the respondents were daily listeners of the community radioprogrammes followed by weekly (30%) and fortnightly (17.33%). Major strengths of CRS identified were interesting dueto local dialect (2.6 MS) followed by quick source of information (2.5 MS), and community participation (2.3 MS). Themajor weaknesses of CRS identified were problems of sustainability (2.5 MS), followed by low (15 kms) coverage (2.3MS), low power (50 W) transmitter (2.00 MS) and no operating cost (1.8 MS). Also listening pattern of the respondentsrevealed that 57.33 per cent listeners were listening CR programme and simultaneously doing some work like cooking,feeding animals, milking etc. followed by about 23 per cent respondents were listening and taking notes.